Effects of formal instruction on second language acquisition - MOUMENE, Ahmed (Journal of Human Sciences, 2006)
This article attempts to put light on the potential effects of grammar instruction on Second / Foreign Language Acquisition. In the last decades, some well-known researchers have cast doubt on the utility of formal instruction for speaking and writing correctly. We will examine recent theoretical and empirical research literature in order to find out the dominant stand amongst researchers regarding the real effects of any focus on form on subsequent language acquisition